Organizational justice and conflict: Do perceptions of fairness influence disagreement?. Issue 3 (August 2015) - Kerwin, Shannon; Jordan, Jeremy S.; Turner, Brian A.
Highlights Examined the relationship between multiple forms of organizational justice and intragroup conflict. Procedural, interactional, and informational justice predicted intragroup conflict. Distributive justice was not a significant predictor of intragroup conflict.